Preparação e caracterização de complexos de inclusão formados entre acetato de hecogenina e β-ciclodextrina - Carvalho, Yasmim Maria Barbosa Gomes de (2016)
The formation of inclusion complexes (IC) with cyclodextrins (CDs) for natural and synthetic compounds have been a major resources employed by the pharmaceutical industry in recent years, the main aim of this IC is increasing the water solubility of poorly soluble drugs by improving its stability and bioavailability. Among the different kind of CDs, the -cyclodextrin (-CD) is mostly used since it is obtained with a high yield and low cost, as well as by presenting appropriate size to accommodate a wide variety of lipophilic substances. Thus, the formation of IC hecogenin acetate / β-CD (HA/β-CD) shows favorable results, saponin belonging to the class of steroidal glycosides with pharmacological activities described in the literature, such as: anti-hyperalgesic, anti-inflammatory and analgesic, it has limited solubility in aqueous medium with formation of persistent and abundant foam. Thus, this study aimed to prepare and characterize IC HA/ β-CD in molar ratios of 1: 1 and 1: 2 (AH: β-CD). The results demonstrated that freeze-dryer (FD) in a molar ratio of 1:2 was the best complexing method, since the DSC and TG/DTG curves was possible to observe respectively the disappearance of the characteristic event of fusion of the HA and considerable reduction in weight loss in the first stage (m1 = 5.62 ± 0.64% from 30-270 ° C), with increased degradation temperature (247 ° C to 300 ° C), indicating greater thermal stability. The FTIR spectrum showed variations in intensity and shift bands between 1739 cm-1 and 1703 cm-1 characteristic carbonyl groups of the ketone and ester of HA. SEM analysis showed the loss of the crystal structure and decrease particle size; the XRD results showed decreased intensity and the appearance of new peaks, suggesting change of crystalline phase to mass spectrometry and docking showed interaction between HA and -CD and NMR confirmed the formation of IC by the FD method on the molar ratio 1: 2. Therefore, it is conclude that from the results, the best method of preparation of IC was observed in FD method in molar ratio 1: 2.